Inklusivitas dan Harmonisasi Pendidikan Berbasis Keagamaan Kristen Dan Katolik di Kabupaten Bangkalan - Klaudius Febrianto Ari Suseno; Indra Jaya Kusuma Wardhana (Journal of Social, Culture, and Language, 2024)
This research investigates the dynamics of Christian and Catholic educational pluralism in Bangkalan Regency with a focus on challenges, inclusivity and efforts to build interfaith harmony. Bangkalan Regency is a region rich in religious diversity, encompassing Christian, Catholic and other religious communities. This study explores the concrete challenges faced by Christian and Catholic educational institutions in managing religious diversity in their environment. The research method involved observation, in-depth interviews and document analysis to understand the perspectives of students, teachers and parents and identify the inclusivity strategies that have been implemented. The results show that despite challenges, Christian and Catholic educational institutions in Bangkalan have taken proactive steps to build inclusive educational environments and strengthen interfaith harmony. This research provides valuable insights for the development of more inclusive and harmonious educational approaches in multicultural societies and contributes to the theoretical understanding of educational pluralism in Indonesia. Keywords: Religion, Multicultural, Education, Pluralism